Namibia’s Regional Libraries: Interim Report of the Regional Study and Resource Center (RSRC) Evaluation - Coward, Chris; Fellows, Michelle; Koepke, Lucas; Rothschild, Chris; Yim, Moonjung (Technology & Social Change Group, 2019)
The Technology & Social Change Group (TASCHA) at the University of Washington’s Information School was commissioned by the Millennium Challenge Corporation (MCC) to conduct a performance evaluation of Namibia’s regional libraries, officially called the Regional Study and Resource Centers (RSRC) Activity. The Activity included the construction of three regional libraries in underserved areas of Namibia in an effort to improve access to information resources, training materials and programs, and study facilities. The performance evaluation comprises a set of quantitative and qualitative data collection efforts and was designed to serve the needs of two major stakeholders, MCC and the Namibia Library and Archives Service (NLAS), as well as the citizens of Namibia and the United States for accountability purposes. This interim report is the second of three evaluation reports and focuses on RSRC operations, services, and usage.
Keywords: Libraries; Regional Resource and Study Center; RSRC; Namibia; evaluation; ICTD; ICT4D; M&E; impact; Millennium Challenge Corporation; MCC